Lessons from an elderly patient with pulmonary embolism caused by protein S deficiency: a case report - Liu Qiang; Li Hong; Shen Min; Wang Hongping; Chen Xian; Li Tianlang (Journal of Medical Case Reports, 2024)
Abstract Background Lower limb deep vein thrombosis (DVT) concurrent with pulmonary embolism (PE) is perilous, particularly in the elderly, exhibiting heterogeneity with thrombophilia mutations. Tailored treatment is essential, yet sudden deaths complicate causative factor elucidation. This report emphasizes genetic testing necessity in PE patients with thrombophilia indicators, facilitating cause identification, personalized treatment guidance, and family education. Case presentation This study details a 75-year-old Chinese woman with DVT and PE, where genetic testing identified thrombophilia, guiding personalized treatment decisions. Results Upon admission, the patient, after over 10 days of bed rest, presented chest tightness, shortness of breath, and unilateral leg swelling. Diagnostic measures revealed DVT and a substantial PE. Genetic testing identified a PROS1 gene C200A>C mutation, reducing protein S activity. Following 2 weeks of anticoagulation and inferior vena cava filter insertion, the patient, discharged, initiated lifelong anticoagulant therapy. A 1-year follow-up showed no recurrent thrombotic events. Family members carrying the mutation received informed and educational interventions. Conclusion Genetic testing for thrombophilic predisposition post-PE is crucial, elucidating etiology, guiding individualized treatment, and playing a pivotal role in family education.